PENGUMPUL SAMPAH PERLU MENDAPATKAN PELAYANAN KESEHATAN KERJA : LITERATUR REVIEW - Mulyanasari, Fertin; Mulyono, Sigit (Jurnal Endurance, 2019)
Waste pickers are a group of workers who are at risk of accidents and work-related diseases because they are exposed to sources of disease from rubbish piles. Various diseases and work accidents occur in waste pickers in various countries. To describe occupational health and safety problems that occur in waste pickers as well as efforts that can be made to improve occupational health and safety of waste pickers. Literature search through online databases on ScienceDirect, Wiley Online, and ProQuest with the keywords used "occupational health service", "occupational health nursing", "waste picker", and "scavenger" obtained a total of 3,624 articles, carried out reviews resulting in 17 selected articles. Health problems and workplace accidents of waste pickers range from respiratory problems, musculoskeletal problems, communicable and non communicable diseases, mental health problems and other problems to impacting their families and causing death. Policies are needed to regulate the health and work safety of waste pickers as well as to improve knowledge of occupational health and safety, providing Persolan Protective Equipment (PPE) and improving waste picker obedience to use PPE by health care program.  Pengumpul sampah merupakan kelompok pekerja yang berisiko terhadap kecelakaan dan penyakit akibat kerja karena terpapar sumber penyakit dari tumpukan sampah. Berbagai penyakit dan kecelakaan kerja terjadi pada pengumpul sampah diberbagai negara. Untuk mendeskripsikan masalah kesehatan dan keselamatan kerja yang terjadi pada pengumpul sampah serta upaya yang dapat dilakukan untuk meningkatkan kesehatan dan keselamatan kerja pengumpul sampah. Pencarian literatur melalui online database  pada ScienceDirect,  Wiley Online, dan ProQuest dengan kata kunci yang digunakan yaitu “occupational health service”, “occupational health nursing”, “waste picker”, dan “scavenger” didapatkan total 3.624 artikel, dilakukan review sehingga dihasilkan 17 artikel terpilih. Masalah kesehatan dan kecelakaan kerja pengumpul sampah beragam mulai dari masalah pernapasan, masalah muskuloskeletal, penyakit menular dan tidak menular, masalah mental dan masalah lainnya hingga berdampak pada keluarga mereka dan menyebabkan kemantian. Diperlukan kebijakan yang mengatur kesehatan dan keselamatan kerja pengumpul sampah serta peningkatan pengetahuan kesehatan dan keselamatan kerja, pengadaan alat pelindung diri dan meningkatkan kepatuhan penggunaan alat pelindung diri oleh pengumpul sampah melalui peran pelayanan kesehatan.